National reports and selected papers (FAO RomeIT, 1992)
Deals with the shrimp fishery of the region; the use of escape panels for fish in shrimp trawl nets; and, artisanal shrimp fishery of the northern coast of Venezuela. Reviews the shrimp fisheries and resources of the Guyana-Brazil continental shelf.
DC